Implementation of Good Corporate Governance, Internal Audit, and Whistleblowing System Against Fraud Prevention - Dinda Ashilah; Yuha Nadhirah; Diana Fajarwati (International Journal of Business and Quality Research, 2023)
The purpose of this study is to see whether or not there is an effect of the implementation of good corporate governance, internal audit, and whistleblowing system on fraud prevention. The size of the board of commissioners, independent commissioners, managerial ownership, and institutional ownership are used as proxies for good corporate governance. This research is a quantitative research using secondary data obtained indirectly. This research was conducted through the company's official website and the Indonesia Stock Exchange (IDX) by accessing the official website of the Indonesia Stock Exchange (IDX), namely www.idx.co.id. The number of samples in this study were 11 BUMN companies for the 2017-2021 period. The data analysis technique in this study used multiple linear regression analysis. The results of this study indicate that the variable size of the board of commissioners and the whistleblowing system has a positive and significant effect on fraud prevention. Independent commissioners, managerial ownership, institutional ownership, and internal audit have no effect on fraud prevention.